PHAGOCYTE FUNCTIONS OF HUMAN SUBJECTS LIVING IN HIGH LEVEL OF NATURAL RADIATION AREAS IN IRAN - Molaie, Molaie Y; Latifynia, Latifynia A; Kalamzadeh, Kalamzadeh A; Abofazeli, Abofazeli T; Nuraie, Nuraie M; Khansarii, Khansarii N (Journal of Ayub Medical College Abbottabad, 2012)
Background: Iran is considered as one of the countries which are located in high radiation area. Ramssar contains natural radioactive sources (Uranium-238) that can produce Radium-226 with high solubility and Radon gas with ability to fuse in dirt, soil, and water in its decay chain. Radioactive rays can produce free radicals with a short life time but high energy, which lead to changes structures of protein bindings, hormones activity, lipids oxidation and DNA breakage which can induce autoimmune diseases and other disorders. The aim of this study was to evaluate effects of natural radiation on innate and humoral immune response of those exposed to natural radioactive rays compared to control group. Methods: Subjects from high and low natural radiation areas were included in the study. Neutrophil chemotaxis, Nitro-Blue Tetrazolium (NBT), and antioxidant effects were evaluated for effects of radioactivity on free radicals and innate immunity. Also Cytokines (IL-2, IL-4) levels for humoral immune system of the subjects were measured. Results: Total plasma antioxidant level and potency of respiratory burst in individuals who lived in area with high levels of natural radiation decreased significantly compared with, control subjects who lived in the other areas of Ramssar with normal radiation. The level of IL-4 increased in individuals who lived in area with high levels of natural radiation, which could lead to Th2 pattern of immune response whether neutrophils chemotaxis in the groups living in the area with high level of natural radiation didn't change significantly when compared to control. Conclusion: Neutrophil respiratory burst activities suggested that NADPH probably reduced due to different reasons including decrease in NADPH oxidase and other enzymes, and mutation of the genes or production of oxidant substances. Neutrophil chemotaxis reduced but this reduction was not statistically significant. Keywords: Radiation, Antioxidant, IL-2, IL-4, chemotaxis, NBT, free radicals